Postharvest processing of green banana - Dhake, Kushal; Jain, S K; Kumar, Arun; Lakawat, S S; Jain, H K (Journal of Postharvest Technology, 2020)
India being a largest producer and consumer of banana in the world and its area and production has been increasing at a fast pace, the post-harvest  losses of this highly nutritious fruits are quite serious in our country. Generally wastage of this fruit before it reaches the consumer is due to lack of proper  processing and storage facilities. Therefore in order to overcome these losses, one effective method would be by converting it into various commercial  banana products. India is the largest producer and consumer of banana and it shares about 33.4 per cent of the total fruit production of country. Green  banana cannot be eaten as raw, hence further processing is required. Green banana peel contains many medicinal properties and health benefits. About  2.5 per cent of production of banana is processed different types of value added products such as fried chips, dehydrated chips, pulp, powder and green  banana peel soups, peel chutney etc. These products are gaining wide popularity in our day-to-day life due to change in life style. The development of  value added products in production catchment area will improve the market effectiveness and add extra income to the farmers which will help in  enhancing their economic conditions and generate employment for rural youth.
Keywords: Green banana; Value addition; banana peel; Health benefits